MANAJEMEN SISTEM LINGKUNGAN SEKOLAH ADIWIYATA MANDIRI (Studi Kasus di SMA Negeri I Lamongan) - Victor Imaduddin Ahmad (Universitas Islam Lamongan, 2017)
Developing environmental system littered fully with cultural values and sense of caring for nature is a concrete manifestation of man's role as caliph. Schools as educational institutions have become a strategic place to develop, implement and disseminate the noble role of man. On this stand, there should be a management which starts from a process of planning well-structured programs and the implementation of the programs consistently. In this context, to achieve a predicate so-called Adiwiyata Mandiri, SMA Negeri 1 Lamongan, has reformed the system of school environment that is broadly performed on four aspects integratively. The four aspects are, firstly, environment oriented-school policies, secondly, environment based-curriculum, thirdly, participatory based-school activities and fourthly, environmentally friendly school infrastructure management. The management of developing the system of education milieu in SMA N 1 Lamongan has eventually brought significant impacts: (1) increasing insight of entire school community of environment, (2) increasing sense of caring for environment of school community. (3) increasing environmental health and safety. (4) improved achievement seen from the trend of increasing number of admissions at state universities. And externally (5) In 2014 the Community Satisfaction Index (HPI) was quite good. This can be explained by the logic that when environment is healthy and comfortable, the school community will be be calm and comfortable, working conditions of teachers and employees become quite excited.Keywords: Management, environmental system, education